How Negative eWOM Affects Purchase Intention: Evidence from Indonesian Traveling Apps Users - Audry Dwithabakti Tungki; Tengku Ezni Balqiah (Jurnal Manajemen Teknologi, 2023)
Abstract. Traveling apps are effective tools to search information and purchase tourism products. Online reviews are the most influential information source in the tourism industry. This study determines the effect of eWOM factors: informational determinants (perceived eWOM usefulness and eWOM perceived credibility of online reviews); personal determinants (using experience of eWOM and product involvement); and the effects of negative reviews (perceived diagnosticity of negative reviews and negative review impression) on purchase intention in traveling applications through some mediating variables (attitude toward online review, attitude toward product, attitude toward brand, and eWOM adoption). This study uses Information Adoption Model and integrates consumer attitude. There were 356 respondents collected through online survey and purposive sampling. Further, Structural Equation Modeling was employed to analyze 17 hypotheses. The results showed that only perceived credibility of online review has no indirect impact on purchase intention. It exhibits the importance role of consumers' attitude and eWOM adoption as mediating variables in promoting purchase intention. This study contributes to industry, especially traveling application managers to arrange their eWOM strategies and travel product providers in managing their brand activities. Keywords: Online review, negative eWOM, Information Adoption Model. Abstrak. Aplikasi traveling efektif digunakan untuk mencari informasi dan membeli produk wisata. Ulasan online adalah sumber informasi paling berpengaruh dalam industri pariwisata. Studi ini menganalisis pengaruh faktor eWOM: informational determinants (perceived eWOM usefulness dan perceived eWOM ecredibility of online reviews), personal determinants (using experience of eWOM dan product involvement), serta effects of negative reviews (perceived diagnosticity of negative reviews dan negative review impression) terhadap purchase intention dalam aplikasi traveling dengan beberapa variabel mediasi (attitude terhadap online review, attitude terhadap produk, attitude terhadap brand, dan eWOM adoption). Penelitian ini menggunakan Information Adoption Model. Terdapat 356 respon yang dikumpulkan melalui survei online dengan purposive sampling. Structural Equation Modeling digunakan untuk menganalisis 17 hipotesis. Hasil penelitian menunjukkan bahwa hanya perceived credibility of online review tidak memiliki dampak tidak langsung terhadap purchase intention. Penelitian ini menunjukkan pentingnya peran sikap konsumen dan adopsi eWOM sebagai variabel mediasi dalam meningkatkan purchase intention. Penelitian ini memberikan kontribusi kepada industri, khususnya pengelola aplikasi perjalanan untuk mengatur strategi eWOM mereka dan penyedia produk perjalanan dalam mengelola aktivitas merek mereka. Kata kunci: Online review, eWOM negatif, Information Adoption Model.